Strategi Pemasaran Wisata Budaya Berbasis E-Marketing Terhadap Minat Kunjungan Wisatawan Desa Wisata Siantar Sitiotio Kecamatan Narumonda Kabupaten Toba - M. Daud Siregar (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2023)
There are numerous cultural tourism attractions in Siantar's tourist village of Sitiotio. This settlement is located in North Sumatra's Narumonda District of the Toba Regency. The Toba Batak culture is distinct and extensive in this area. This village is a fantastic location to visit if you want to learn about the local way of life. The unusual cultures found in this village include the TorTor dance, Batak cuisine, traditional Batak homes, handicrafts, and Batak rituals. There are still not many visitors to Siantar Sitiotio Tourism Village. Lack of easy and quick access to information and inadequate promotion of this tourist resort to potential visitors may be the root of the problem. Therefore, an internet-based cultural tourism marketing strategy must be put into place in order to increase the number of tourists to Siantar Sitiotio Tourism Village. . In this work, the analysis was conducted using a quantitative approach. where numerical data is processed and examined to obtain the underlying scientific information. This study also discovered that e-marketing can spur visitors' interest in tourist destinations. Using a straightforward linear regression analysis, the impact of the two variables—the independent variable and the dependent variable—is quantified. The E-Marketing Based Cultural Tourism Marketing Strategy (X) variable has a consistency value of 200 units, which implies that after adding 1%, the value rises by 597 units. The direction of the E-Marketing Based Cultural Tourism Marketing Strategy (variable X) is positive, as shown by the regression coefficient. It can be deduced that the variable E-Marketing Based Cultural Tourism Marketing Strategy (X) impacts the variable Interest in Tourist Visits at Siantar Sitiotio Tourism Village, Narumonda District, Toba Regency since the sig value of the table above is 0.000 more than 0.05. There are numerous cultural tourism attractions in Siantar's tourist village of Sitiotio. This settlement is located in North Sumatra's Narumonda District of the Toba Regency. The Toba Batak culture is distinct and extensive in this area. This village is a fantastic location to visit if you want to learn about the local way of life. The unusual cultures found in this village include the TorTor dance, Batak cuisine, traditional Batak homes, handicrafts, and Batak rituals. There are still not many visitors to Siantar Sitiotio Tourism Village. Lack of easy and quick access to information and inadequate promotion of this tourist resort to potential visitors may be the root of the problem. Therefore, an internet-based cultural tourism marketing strategy must be put into place in order to increase the number of tourists to Siantar Sitiotio Tourism Village. . In this work, the analysis was conducted using a quantitative approach. where numerical data is processed and examined to obtain the underlying scientific information. This study also discovered that e-marketing can spur visitors' interest in tourist destinations. Using a straightforward linear regression analysis, the impact of the two variables—the independent variable and the dependent variable—is quantified. The E-Marketing Based Cultural Tourism Marketing Strategy (X) variable has a consistency value of 200 units, which implies that after adding 1%, the value rises by 597 units. The direction of the E-Marketing Based Cultural Tourism Marketing Strategy (variable X) is positive, as shown by the regression coefficient. It can be deduced that the variable E-Marketing Based Cultural Tourism Marketing Strategy (X) impacts the variable Interest in Tourist Visits at Siantar Sitiotio Tourism Village, Narumonda District, Toba Regency since the sig value of the table above is 0.000 more than 0.05.